Pancasila Village as a Role Model of Local Wisdom-Based Religious Moderation in Lamongan Regency - Sutopo Sutopo; Ahmad Burhan Hakim; Muhammad Haris; Ulil Amri (JURNAL AT-TURAS, 2024)
Balun Village in Turi sub-district, Lamongan Regency, known as a Pancasila Village, is one example of religious abstinence based on local wisdom. The aims of study are to:(1) identify the implementation of Pancasila Village as a demonstrate for devout control, (2) get it the points of view and parts of devout and community pioneers related to Pancasila Village, and (3) create the village as a demonstrate for devout control. This study was conducted in Baran Village employing a subjective approach. Information collection was carried out through in-depth interviews, documentation, and perception with key witnesses, and youth pioneers. The discoveries demonstrate that: 1) The implementation of Pancasila Village in Lamongan has succeeded through mutual tolerance and not the imposition of religious beliefs. 2) Religious and community leaders in Baran Village effectively communicate and prioritize common interface. 3) An interesting finding is the existence of a multi-religious grave digging team in the village.